Daily rhythms are retained both in spontaneously developed sarcomas and in xenografts grown in immunocompromised SCID mice. (October 2014) - Comas, Maria; Kuropatwinski, Karen K.; Wrobel, Michelle; Toshkov, Ilia; Antoch, Marina P.
<x xml:space="preserve">Abstract</x> The circadian clock generates and regulates many daily physiological, metabolic and behavioral rhythms as well as acute responses to various types of stresses including those induced by anticancer treatment. It has been proposed that modulatory function of the clock may be used for improving the therapeutic efficacy of established anti-cancer treatments. In order to rationally exploit this mechanism, more information is needed to fully characterize the functional status of the molecular clock in tumors of different cellular origin; however, the data describing tumor clocks are still inconsistent. Here we tested the status of clock in two models of tumors derived from connective tissue: sarcomas spontaneously developed in p53-deficient mice and human fibrosarcoma cells grown as xenografts in immunocompromised severe combined immunodeficient (SCID) mice. We show that both types of tumors retain a functional clock, which is synchronized in phase with normal tissues. We also show that spontaneously developed tumors are not only oscillating in the context of an organism where they receive hormonal and metabolic signals but continue oscillating ex vivo in tissue explants demonstrating that tumors have functional clocks capable of timing all their functions. We also provide evidence that similar to liver, tumors can be synchronized by food availability independent of the central pacemaker in the suprachiasmatic nuclei (SCN). These data provide the basis for the design of anticancer therapies that take into account the circadian metabolic and physiological patterns of both the tumor and normal tissues.